Chess and corporate strategy - Desiata, Luca (Routledge, 2025)
"Chess and Corporate Strategy is an intriguing journey through cognitive psychology, artificial intelligence and game theory. The innovative methodology employed by the author leverages the metaphor of chess to furnish a compendium of corporate strategy, including strategic thinking, decision-making, negotiations and leadership. This book provides the reader with the insights and strategies of chess champions, without the need for years of study and practice. Throughout the book, captivating episodes from the rich history of the game of chess weave seamlessly, elevating the reading experience beyond that of a conventional management publication. Every chapter is enriched by insightful interviews featuring Anatoly Karpov, the 12th chess world champion. Karpov adeptly illustrates the practical application of theoretical concepts in the professional realm through real-life examples. This book will be a valuable resource to leaders and executives interested in innovative ways of thinking about corporate strategy and the running of a business"-- Provided by publisher.
Keywords: Strategic planning.; Game theory.; Chess.; elektronické knihy; electronic books